A new avocado pest in Central America (Lepidoptera: Tortricidae) with a key to Lepidoptera larvae threatening avocados in California - Gilligan, Todd M.; Brown, John W.; Hoddle, Mark S. (Zootaxa, 2011)
Cryptaspasma perseana Gilligan and Brown, new species, is described and illustrated from Mexico and Guatemala. This species is a potential pest of the fruit of cultivated avocado, Persea americana (Lauraceae). Images of adults, male secondary structures, male and female genitalia, eggs, larvae, and pupae are provided. Details of the life history are reviewed. We provide characters to differentiate this pest from the most common avocado fruit pest in the region, Stenoma catenifer (Walsingham) (Elachistidae), and a key to identify Lepidoptera larvae threatening avocado in California. In addition, we provide a complete list of tortricids documented from different avocado varieties worldwide.